Prognostic Value of the Lactate/Albumin Ratio for Mortality in Sepsis-Associated Acute Kidney Injury: A Systematic Review and Meta-Analysis - Tanjung, Fariz Fadhly; Wijaya, Wan Novriza; Anggraeni, Novita; Hidayat, Nopian; Muharrami, Vera; Irawan, Dino (JAI (Jurnal Anestesiologi Indonesia), 2026)
Objectives: Early risk stratification in patients with sepsis-associated acute kidney injury (SA-AKI) remains challenging because conventional clinical markers have limited prognostic accuracy. The lactate/albumin ratio (LAR), reflecting metabolic stress and systemic inflammation, has emerged as a potential prognostic biomarker. This systematic review and meta-analysis aimed to evaluate the prognostic value of LAR for mortality prediction in adult patients with SA-AKI.Study design: A systematic review and meta-analysis were conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Observational cohort studies reporting adjusted hazard ratios (HRs) for the association between LAR and mortality in adult patients with SA-AKI were included. Risk of bias was assessed using the Quality in Prognosis Studies (QUIPS) tool. Pooled effect estimates were calculated using a random-effects inverse-variance model.Data sources: The PubMed, Embase, and Web of Science were systematically searched from database inception to July 2025 without language restrictions. Reference lists of relevant articles were also screened to identify additional studies.Data synthesis: Eight studies were included in the systematic review, and six retrospective cohort studies involving more than 25,000 critically ill patients were eligible for meta-analysis. Elevated LAR measured during early ICU admission was independently associated with increased mortality. The pooled hazard ratio comparing the highest versus lowest LAR categories was 1.97 (95% CI: 1.42–2.73), indicating nearly a twofold higher risk of death. This association remained consistent across different populations and mortality endpoints, although substantial heterogeneity was observed (I² = 91%).Conclusions: LAR is a simple, accessible, and cost-effective biomarker for early mortality risk stratification in SA-AKI. Early measurement of LAR in ICU settings might improve the prognosis of mortality risk, thereby helping with timely decision-making.Registration: The protocol for this systematic review was prospectively registered in PROSPERO.